Are novel ecosystems the only novelty of rewilding?. Issue 6 (20th October 2020) - Klop‐Toker, Kaya; Clulow, Simon; Shuttleworth, Craig; Hayward, Matt W.
Abstract : Since the introduction of the term "rewilding" in 1998, several definitions have been proposed, sparking debate around terminology and how (or if) rewilding differs from restoration. Many papers attempt to distinguish between the two terms through a series of descriptive attributes: historic baselines, landscape‐driven transformation, ongoing human intervention, the connection of people with nature, and the creation of novel ecosystems. Here, we discuss the overlap between these terms and illustrate that the creation of novel ecosystems provides the clearest distinction between rewilding and restoration. If the definition of rewilding is distilled down to its most unique component, the creation of novel ecosystems, perhaps scientists can then work to produce a clear framework for rewilding that is based on best conservation practice.